Circulating microRNA after autologous bone marrow mononuclear cell (BM-MNC) injection in patients with ischemic stroke. (17th December 2019) - Mancha, Fernando; Escudero-Martinez, Irene; Zapata-Arriaza, Elena; Vega-Salvatierra, Angela; Cabezas, Juan Antonio; Lebrato, Lucia; Pardo, Blanca; De-La-Torre, Javier; Zapata, Montserrat; Escamilla, Virginia; Calderón-Cabrera, Cristina; Martín-Sánchez, Jesús; et al.
Abstract : Previous studies have shown the potential of microRNAs (miRNA) in the pathological process of stroke and functional recovery. Bone marrow mononuclear cell (BM-MNC) transplantation improves recovery in experimental models of ischemic stroke that might be related with miRNA modifications. However, its effect on circulating miRNA has not been described in patients with stroke. We aimed to evaluate the circulating levels of miRNAs after autologous BM-MNC transplantation in patients with stroke. We investigate the pattern of miRNA-133b and miRNA-34a expression in patients with ischemic stroke included in a multicenter randomized controlled phase IIb trial (http://www.clinicaltrials.gov ; unique identifier: NCT02178657 ). Patients were randomized to 2 different doses of autologous intra-arterial BM-MNC injection (2×10 6 /kg or 5×10 6 /kg) or control group within the first 7 days after stroke onset. We evaluate plasma concentration of miRNA-113b and miRNA-34a at inclusion and 4, 7, and 90 days after treatment. Thirteen cases (8 with 2×10 6 /kg BM-MNC dose and 5 with 5×10 6 /kg dose) and 11 controls (BM-MNC non-treated) were consecutively included. Mean age was 64.1±12.3 with a mean National Institutes of Health Stroke Scale score at inclusion of 14.5. Basal levels of miRNA were similar in both groups. miR-34a-5p and miR-133b showed different expression patterns. There was a significant dose-dependent increase of miRNA-34a levels 4 days after BM-MNC injection (fold change 3.7, p<0.001), whereas miRNA-133b showed a significant increase in the low-dose BM-MNC group at 90 days. Intra-arterial BM-MNC transplantation in patients with ischemic stroke seems to modulate early circulating miRNA-34a levels, which have been related to precursor cell migration in stroke and smaller infarct volumes.